Síntese de feromônios com potencial para o manejo integrado de pragas - Oliveira, Adeildo Junior de (2018)
The insect pheromones have shown considerable efficiency to aid in the control of pests that cause damage agricultural development. The scarcity of these compounds in natural sources places them in the group of molecules whose syntheses are intended. This work aimed to perform the synthesis of the pheromones of the insect pests species H. armigera, S. frugiperda and P. interpunctella, whose pheromonal components are the compounds (Z)-9-hexadecenal and (Z)-11-hexadecenal (H. armigera), (Z)-7-dodecenyl acetate and (Z)-11-hexadecenyl acetate (S. frugiperda), and (Z,E)-9,12-tetradecadienyl acetate (P. interpunctella). The work also aimed to perform a study of optimization of the monobromination reaction of α, ω-diols with HBr, using the solvents toluene, isooctane and 1,2-dicloethane (1,2-DCE), with two different molar proportions of diol-HBr, 1/1 and 1/2 molar equivalents. The preparation of the (Z)-9-hexadecenal and (Z)-11-hexadecenal aldehydes followed a common route, proposed with 6 steps, including the preparation of bromoalcohols under the conditions established in the present work. The synthesis of (Z)-7-dodecenyl and (Z)-11-hexadecenyl acetates was performed by a similar synthetic route, involving an acetylation step. The (Z,E)-9,12-tetradecadienyl acetate pheromonal component did not have its synthesis completed, presenting the third stage finished with the preparation of a terminal alkyne, in a route with 7 reactional steps. The bromoalcohol preparation study showed the 1,2-DCE as a good solvent to replace toluene in diol-HBr with a ratio of 1/2 molar equivalents. The (Z)-9-hexadecenal and (Z)-11-hexadecenal aldehydes were synthesized in overall yields of 35 and 56%, respectively. The (Z)-7-dodecenyl and (Z)-11-hexadecenyl acetates were prepared in overall yields of 53 and 56%, respectively. The routes studied were applicable for the preparation of the final products on preparative scales.